MYH9‐related disease mutations cause abnormal red blood cell morphology through increased myosin‐actin binding at the membrane. Issue 6 (17th April 2019) - Smith, Alyson S.; Pal, Kasturi; Nowak, Roberta B.; Demenko, Anastasiya; Zaninetti, Carlo; Da Costa, Lydie; Favier, Remi; Pecci, Alessandro; Fowler, Velia M.
Abstract: MYH9 ‐related disease ( MYH9 ‐RD) is a rare, autosomal dominant disorder caused by mutations in MYH9, the gene encoding the actin‐activated motor protein non‐muscle myosin IIA (NMIIA). MYH9 ‐RD patients suffer from bleeding syndromes, progressive kidney disease, deafness, and/or cataracts, but the impact of MYH9 mutations on other NMIIA‐expressing tissues remains unknown. In human red blood cells (RBCs), NMIIA assembles into bipolar filaments and binds to actin filaments (F‐actin) in the spectrin‐F‐actin membrane skeleton to control RBC biconcave disk shape and deformability. Here, we tested the effects of MYH9 mutations in different NMIIA domains (motor, coiled‐coil rod, or non‐helical tail) on RBC NMIIA function. We found that MYH9 ‐RD does not cause clinically significant anemia and that patient RBCs have normal osmotic deformability as well as normal membrane skeleton composition and micron‐scale distribution. However, analysis of complete blood count data and peripheral blood smears revealed reduced hemoglobin content and elongated shapes, respectively, of MYH9 ‐RD RBCs. Patients with mutations in the NMIIA motor domain had the highest numbers of elongated RBCs. Patients with mutations in the motor domain also had elevated association of NMIIA with F‐actin at the RBC membrane. Our findings support a central role for motor domain activity in NMIIA regulation of RBC shape and define a new sub‐clinical phenotype of MYH9 ‐RD.